2021
DOI: 10.1002/jts.22769
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of symptom change among veterans receiving an integrated treatment for posttraumatic stress disorder and substance use disorders

Abstract: The present study examined temporal patterns of symptom change during treatment for comorbid posttraumatic stress disorders (PTSD) and substance use disorders (SUDs). We hypothesized that PTSD symptom severity would predict subsequent-session substance use and that this association would be particularly strong among patients who received an integrated treatment versus SUDonly treatment. Participants were 81 United States military veterans with current PTSD and an SUD who were enrolled in a 12-week, randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Psychotherapy interventions for comorbid SUD and PTSD have been the subject of an increasing number of studies over the past two decades (e.g., Bedard-Gilligan et al, 2018;Brady et al, 2004). Research on treatment models has largely focused on two interconnected issues: (a) the effectiveness of integrated treatments for co-occurring PTSD and SUD and (b) the potential harms of engaging in trauma-focused treatment when a co-occurring SUD is active (e.g., Badour et al, 2021;Kehle-Forbes et al, 2019;Tripp et al, 2020). Recent meta-analyses have demonstrated that integrated PTSD and SUD treatments, particularly those that involve a specific trauma focus, are effective at reducing PTSD and SUD symptoms (Roberts et al, 2015(Roberts et al, , 2022Simpson et al, 2021).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Psychotherapy interventions for comorbid SUD and PTSD have been the subject of an increasing number of studies over the past two decades (e.g., Bedard-Gilligan et al, 2018;Brady et al, 2004). Research on treatment models has largely focused on two interconnected issues: (a) the effectiveness of integrated treatments for co-occurring PTSD and SUD and (b) the potential harms of engaging in trauma-focused treatment when a co-occurring SUD is active (e.g., Badour et al, 2021;Kehle-Forbes et al, 2019;Tripp et al, 2020). Recent meta-analyses have demonstrated that integrated PTSD and SUD treatments, particularly those that involve a specific trauma focus, are effective at reducing PTSD and SUD symptoms (Roberts et al, 2015(Roberts et al, , 2022Simpson et al, 2021).…”
mentioning
confidence: 99%
“…One treatment-focused study found that alcohol use during integrated treatment predicted an exacerbation of PTSD symptoms two sessions later (Tripp et al, 2020). However, in another treatmentfocused study, Badour et al (2021) noted that neither substance use (i.e., alcohol, cocaine, marijuana, benzodiazepines, opioids, amphetamines) nor the frequency of use were significant predictors of PTSD symptoms in the next session. The authors also found that opioid use, alone or with other substances, did not predict next-day PTSD symptoms in a nontreatment study of daily monitoring of use and symptoms (Badour et al, 2023).…”
mentioning
confidence: 99%
See 2 more Smart Citations